2021
DOI: 10.17113/ftb.60.01.22.7264
|View full text |Cite
|
Sign up to set email alerts
|

From the Autochthonous Grape Varieties of the Kastav Region (Croatia) to the Belica Wine

Abstract: Research background. Coastal region of Croatia is rich in autochthonous grape varieties. Many of them have been almost abandoned such as the autochthonous varieties of Kastav (Croatia), used for the production of the Kastavska Belica wine. Therefore, the rationale of the presented study was to characterize autochthonous varieties 'Verdić', 'Mejsko belo', 'Jarbola', 'Divjaka' and 'Brajkovac' grape varieties. In addition, we performed a molecular characterization of the corresponding Belica wines. Experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Four coumarin components were in the differential metabolites, the psoralenoside and isopsoralenoside contents decreased, whereas the psoralen and isopsoralen contents increased. It was considered that the glycosidic bonds of psoralenoside and isopsoralenoside were broken during FP processing, and psoralen and isopsoralen were produced by hydrolysis [24] (Figure 3A, B). Studies confirmed that psoralen could stimulate osteoblast proliferation [25], and isopsoralen could promote osteogenic differentiation [26] and prevent osteoporosis [27].…”
Section: Chemical Transformation Mechanismsmentioning
confidence: 99%
“…Four coumarin components were in the differential metabolites, the psoralenoside and isopsoralenoside contents decreased, whereas the psoralen and isopsoralen contents increased. It was considered that the glycosidic bonds of psoralenoside and isopsoralenoside were broken during FP processing, and psoralen and isopsoralen were produced by hydrolysis [24] (Figure 3A, B). Studies confirmed that psoralen could stimulate osteoblast proliferation [25], and isopsoralen could promote osteogenic differentiation [26] and prevent osteoporosis [27].…”
Section: Chemical Transformation Mechanismsmentioning
confidence: 99%
“…In this regard, winemakers expand the existing list of quality indicators with additional criteria at different stages of production [1][2][3]. They also take into account various factors, among which a special attention is paid to soil and climatic conditions of grape growing [4][5][6][7], choice of used grape varieties [8][9][10][11] and yeast races for primary and post fermentation [12][13][14], as well as other technological operations [15][16][17][18]. At the same time, there is not enough information now on a comprehensive systemic assessment of grape and base wine indicators for the production of high-quality sparkling wines, which leads us to carry out this research.…”
Section: Introductionmentioning
confidence: 99%